2011
DOI: 10.1260/0144-5987.29.5.525
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Performance and Combustion Parameters in a Heavy-Duty Diesel Engine Fueled with Iso-Butanol/Diesel Fuel Blends

Abstract: This study discusses the suitability of iso-butanol/diesel fuel blends as an alternative fuel and determines their effects on the performance and combustion characteristics of a heavy-duty diesel engine. For this purpose, various isobutanol/diesel fuel blends containing 5%, 10% and 15% iso-butanol were prepared in volume basis and tested in a turbo-charged, six-cylinder direct injection diesel engine at the speed of 1400 rpm and three different loads (150, 300 and 450 Nm). The results indicate that when the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 35 publications
3
18
0
Order By: Relevance
“…High latent heat of vaporization causes poorer and slower fuel-air mixing that can increase NOx emissions. 49 Thus HC emissions clearly follow the order of cetane index and latent heat of vaporization of the blends as follows (from highest to lowest): n-propanol/diesel > n-butanol/diesel > n-pentanol/diesel blend at bmep = 4.0 bar and speed = 1500 rpm.…”
Section: Hc (Hydrocarbons)mentioning
confidence: 93%
“…High latent heat of vaporization causes poorer and slower fuel-air mixing that can increase NOx emissions. 49 Thus HC emissions clearly follow the order of cetane index and latent heat of vaporization of the blends as follows (from highest to lowest): n-propanol/diesel > n-butanol/diesel > n-pentanol/diesel blend at bmep = 4.0 bar and speed = 1500 rpm.…”
Section: Hc (Hydrocarbons)mentioning
confidence: 93%
“…72 Further the less calorific value, poor miscibility and instability dur-73 ing blending, poor lubricating properties challenge their use in die-74 sel engines [5]. Several have been used to overcome these shortcomings of alcohols as a 77 diesel engine fuel [6]. The use of higher alcohols in diesel engines 78 has gained interest in the recent years with the focus especially 79 on butanol and its isomers [3][4][5][6][7][8][9].…”
mentioning
confidence: 99%
“…Several have been used to overcome these shortcomings of alcohols as a 77 diesel engine fuel [6]. The use of higher alcohols in diesel engines 78 has gained interest in the recent years with the focus especially 79 on butanol and its isomers [3][4][5][6][7][8][9]. Their results showed that buta-80 nol-diesel blends have significantly reduced soot and CO emissions 81 with slight impact in performance.…”
mentioning
confidence: 99%
“…Other factors that also have great influence on the NOx formation are the residence time for the reaction and also the oxygen concentration [63,64]. Figure 9C shows a reduction in raw NOx emissions with the SOI delay in both operating points.…”
Section: Raw Nox Emission Analysismentioning
confidence: 99%